Spatial Distribution and Antioxidant Activity of Extracts from Citrus Fruits - María García-Nicolás; Carlos A. Ledesma-Escobar; Feliciano Priego-Capote (MDPI AG, 2023)
Citrus fruits are recommended components of the human diet because of their enriched composition in bioactive compounds and health benefits. Among their notable components are phenols, with a special emphasis on flavonoids, limonoids, and carboxylic acids. In this research, we have carried out a spatial metabolomics analysis for the characterization of these bioactive families in three citrus fruits, namely, lemons, limes, and mandarins. Sampling was undertaken, for which the juices and three fruit tissues, namely, albedo, flavedo, and segments, were analyzed. This characterization allowed for the determination of 49 bioactive compounds in all the samples. The composition of the different extracts was correlated with the antioxidant capacity measured by the DPPH radical scavenging activity and β-carotene bleaching assays. Flavonoids, found in the albedo and flavedo at higher concentrations, were the main components responsible for DPPH radical scavenging activity. On the other hand, the combined action of flavonoids and limonoids contributed to explaining the antioxidant activity measured by the β-carotene bleaching assay. Generally, the antioxidant capacity of juices was lower than that estimated for extracts from citrus tissues.